2019
DOI: 10.1364/ol.44.004813
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral similarity of dissipative solitons in an ultrafast fiber laser

Abstract: Dissipative solitons are non-dispersive localized waves that exhibit intriguing dynamics. In optical systems, the discovery of new soliton dynamics and how to accurately manipulate dissipative solitons are still largely unexplored and challenging in the ultrafast fiber laser community. Herein, we unveil a new type of dissipative soliton behavior in a net-normal-dispersion bidirectional ultrafast fiber laser. That is, the bidirectional dissipative solitons will always reveal similar spectral and temporal charac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…The counterpart of the spatial non-diffracting beam is the pulsed non-diffracting beam. The ultrashort-pulsed laser could be achieved in the fiber laser using the mode-locking achieved by a saturable absorber or nonlinear polarization rotation [56][57][58]. The pulsed nondiffracting beam includes the pulsed laser beam with the spatially non-diffracting feature or the temporally non-dispersive beam.…”
Section: Pulsed Non-diffracting Beamsmentioning
confidence: 99%
“…The counterpart of the spatial non-diffracting beam is the pulsed non-diffracting beam. The ultrashort-pulsed laser could be achieved in the fiber laser using the mode-locking achieved by a saturable absorber or nonlinear polarization rotation [56][57][58]. The pulsed nondiffracting beam includes the pulsed laser beam with the spatially non-diffracting feature or the temporally non-dispersive beam.…”
Section: Pulsed Non-diffracting Beamsmentioning
confidence: 99%
“…Finally, over the last decade, several works have demonstrated a wide variety of bidirectional lasers operation wavelength, such as at 1.55 and 2 μm in Tm-doped fibre lasers [ 189 , 190 , 191 ], and mode-locked pulse generation regimes by varying net cavity dispersion [ 192 , 193 , 194 ]. However, according to the Sagnac Equations ( 3 ) and ( 4 ), the application of shorter operation wavelengths is more beneficial for increasing the overall sensitivity to rotation.…”
Section: Ultrafast Lasersmentioning
confidence: 99%
“…Further progress in bidirectional ultrafast fibre laser development demonstrated their potential for applications in detecting angular movements [25][26][27] and dual-comb spectroscopy 28,29 . Y. Yu et al demonstrated the similarity of dissipative solitons build-up dynamics in bidirectional mode-locked laser with normal-net cavity dispersion 30 . Still, the reports on the fundamentals of bidirectional ultrafast generation are rare.…”
mentioning
confidence: 99%